The Contribution of Digital Health in the Response to Covid-19 in Vietnam - Bui, Long Viet; Ha, Son Thai; Nguyen, Ha Ngoc; Nguyen, Truong Thanh; Nguyen, Thuy Phuong; Tran, Kien; Tran, Tuyen Van; Nguyen, Tu Huu; Tran, Thong Huy; Pham, Nghiem Duc; Bui, Hanh My (Frontiers in Public Health, 2021)
Emerging from early of 2020, the COVID-19 pandemic has become one of the most serious health crisis globally. In response to such threat, a wide range of digital health applications has been deployed in Vietnam to strengthen surveillance, risk communication, diagnosis, and treatment of COVID-19. Digital health has brought enormous benefits to the fight against COVID-19, however, numerous constrains in digital health application remain. Lack of strong governance of digital health development and deployment; insufficient infrastructure and staff capacity for digital health application are among the main drawbacks. Despite several outstanding problems, digital health is expected to contribute to reducing the spread, improving the effectiveness of pandemic control, and adding to the dramatic transformation of the health system the post-COVID era.